MINAT BACA DAN KEBIASAAN MENCONTEK DALAM HASIL BELAJAR MEMAHAMI TEKS DISKUSI SISWA KELAS IX SMP N 1 PARIAMAN - Fitri, Julia (Universitas Negeri Surabaya, 2019)
Reading interest is one of the important things in understanding classroom learning. However, reading interest at this time is still a problem faced by teachers in schools. This study aims to: (1) describe the reading interest of class IX SMP N 1 Pariaman students, (2) describe the learning outcomes to understand the description text of class IX SMP N 1 Pariaman students, and (3) describe the relationship between reading interest and learning outcomes discussion of class IX students of SMP N 1 Pariaman. This research is a qualitative descriptive study using the description method. Interest in reading and learning outcomes are described in several points. The results of this study indicate that there is a correlation between reading interest and learning outcomes understanding the discussion text of class IX SMP N 1 Pariaman.